The Impact of Digital Communications on Consumer Perceptions of Sport Celebrity Transgressions. Issue 2 (3rd April 2018) - Sassenberg, Anne-Marie; Summers, Jane; Johnson-Morgan, Melissa; Hassan, Rumman
ABSTRACT: Whilst the use of sport celebrities in marketing strategies is growing in popularity it is not without risk. The increasing reliance on scandal by the news media to capture audience attention, has accelerated the interest in sport-celebrity transgressions. This research adopts an netnographic method to analyze over seven thousand comments from online forums about sport celebrity transgressions. We found that consumers were more likely to express negative comments in relation to transgressions that violated moral, ethical and/or legal norms and that this in turn was most likely to effect the perceived role model ability of a sport celebrity. We provide evidence that the communication behavior of sport fans in a digital communication medium extends the life of a transgression in the public domain. Finally, we noted sport fans exhibited higher levels of engagement and willingness to participate in debate in these mediums than observed in other types of online communities.